Penggunaan Linear Programming pada Optimalisasi Lahan Sempit di Desa Jatimulyo Kecamatan Jati Agung Kabupaten Lampung Selatan - Widia Sari, Tri; Abidin, Zainal; Adawiyah, Rabiatul (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2025)
This research aims to analyze the most appropriate planting pattern to obtain optimal income on a small land area in Jati Mulyo Village, Jati Agung District, South Lampung Regency. Samples were taken purposively from 15 farmers who cultivated rice-rice-vegetable, rice-vegetable and rice-vegetable-corn planting patterns. The data analysis used is qualitative and quantitative descriptive methods, as well as linear programming methods which are analyzed using Microsoft Excel 2010 software with the addition of Excel Solver. The results of the analysis show that the rice-vegetable planting pattern and the rice-vegetable-corn planting pattern are the right planting patterns to obtain optimal income with a coefficient of 3.376 for the rice-vegetable planting pattern and 2.404 for the rice-vegetable-corn planting pattern, and 0 for rice-rice-vegetable planting pattern. The optimal income is Rp 55,706,125 consisting of Rp 27,092,289 for income from the rice-vegetable planting pattern and Rp 28,613,836 for income from the rice-vegetable-corn planting pattern with land area and labor constraints.